End-Triassic Extinction in a Carbonate Platform From Western Tethys: A Comparison Between Extinction Trends and Geochemical Variations - Todaro, Simona; Rigo, Manuel; Di Stefano, Pietro; Aiuppa, Alessandro; Chiaradia, Massimo (Frontiers in Earth Science, 2022)
The Triassic/Jurassic boundary section cropping out at Mt Sparagio in north-western Sicily (Italy) consists of a thick and continuous peritidal succession typical of a Tethyan carbonate platform. The combined chemostratigraphic and biostratigraphic study of this section allowed us to parallel the environmental variations inferred by the isotopic records and the extinction trends recorded by the benthic organisms. In the studied section, the isotope data of C, O, and S are indicative of serious environmental perturbations related to the CAMP activity, as recorded worldwide. Two negative excursions in the C-curve (Initial-CIE and Main-CIE) confirm the acidification processes that affected the benthic community. Moreover, the oxygen isotopes curve indicates a strong warming-trend that corresponds to the reduction in biodiversity and size of the megalodontoids in the upper part of the Rhaetian beds, probably due to the deterioration of the photosymbiotic relationships of these pelecypods. Finally, we also present some novel isotope data (Zn, Pb, Sr) from the Mt Sparagio section that offer additional clues on a tight control of CAMP volcanism on the End-Triassic Extinction.